British Thoracic Society survey of rehabilitation to support recovery of the post-COVID-19 population. Issue 12 (2nd December 2020) - Singh, Sally J; Barradell, Amy C; Greening, Neil J; Bolton, Charlotte; Jenkins, Gisli; Preston, Louise; Hurst, John R
Abstract : Objective: A proportion of those recovering from COVID-19 are likely to have significant and ongoing symptoms, functional impairment and psychological disturbances. There is an immediate need to develop a safe and efficient discharge process and recovery programme. Established rehabilitation programmes are well placed to deliver a programme for this group but will most likely need to be adapted for the post-COVID-19 population. The purpose of this survey was to rapidly identify the components of a post-COVID-19 rehabilitation assessment and elements of a successful rehabilitation programme that would be required to deliver a comprehensive service for those post-COVID-19 to inform service delivery. Design: A survey comprising a series of closed questions and a free-text comment box allowing for a qualitative analysis. Setting: Online survey. Participants: Multiprofessional clinicians across specialties were invited to take part. Results: 1031 participants responded from a broad range of specialties. There was overwhelming support for an early posthospital discharge recovery programme to advise patients about the management of fatigue (95% agreed/strongly agreed), breathlessness (94%) and mood disturbances (including symptoms of anxiety and depression, 92%). At the time point of 6–8 weeks, an assessment was considered important, focusing on a broad range of possible symptoms and supporting a return to work. Recommendations for the intervention described a holistic programme focusing on symptom management, return of function and return to employment. The free-text comments added depth to the survey and the need 'not to reinvent the wheel' but rather adapt well-established rehabilitation services to individually tailor needs-based care with continued learning for service development. Conclusion: The responses indicate a huge interest and the urgent need to establish a programme to support and mitigate the long-term impact of COVID-19 by optimising and individualising existing rehabilitation programmes.